GE_GERICHTE C/2518/2017 vom 8. November 2017 - GE Cour de justice (2017)
MAINLEVÉE PROVISOIRE ; PROCÉDURE SOMMAIRE ; SUSPENSION DE LA PROCÉDURE ; RECONNAISSANCE DE DETTE | CPC.253; CPC.256; CPC.126; LP.821;